POTENSI TUMPANG TINDIH PENERAPAN PENGEMBALIAN KEUNTUNGAN TIDAK SAH TERHADAP INVESTOR PASAR MODAL OLEH OTORITAS JASA KEUANGAN (Lex Jurnalica, 2021)
The capital market is growing and rapidly increasing by investors cannot be avoided from the practice of violations by irresponsible persons that cause losses to investors. Therefore, Financial Services Authority issued POJK No. 65/POJK.04/2020 to provide legal protection for investors so that a conducive capital market ecosystem can be realized. Forms of legal protection are repayment of ill-gotten gains and distribution of funds to compensate investors for their losses. In POJK No. 65/POJK.04/2020, there is a potential for overlapping with Law of the Republic of Indonesia Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations which will hinder the legal purpose of providing fairness and certainty for capital market investors.